Agglomeration of Nanoparticles Inhibits Solvent‐Driven Ligand Stripping - Akhlak U. Mahmood; Mehedi H. Rizvi; Joseph B. Tracy; Yaroslava G. Yingling (Advanced Materials Interfaces)
Abstract The colloidal stability of nanoparticles (NPs) is significantly affected by complex solvent‐ligand interactions, with poor solvents often inducing NP agglomeration and ligand desorption from the surface. Despite the frequent occurrence of these phenomena in post‐synthetic experiments, the underlying mechanisms remain elusive. In this study, dynamic light scattering (DLS), thermogravimetric analysis (TGA), and large‐scale all‐atom molecular dynamics (MD) simulations are used to investigate solvent‐driven oleylamine ligand removal from Fe3O4 NPs. Eight experimentally relevant NP systems under replicated solvent conditions are modeled, enabling direct comparison and yielding deep insights into solvent‐mediated ligand stripping with excellent agreement. These findings reveal that ethanol's ability to strip oleylamine ligands from Fe3O4 NPs is impeded by NP agglomeration, where stripped and interdigitated ligands create a steric barrier, preventing solvent molecules from accessing the NP surface. This effect becomes more pronounced with increasing NP size due to the greater ligand surface density that enhances interdigitation. Moreover, the presence of a threshold concentration of the poor solvent in binary mixtures is identified, below which the maximum number of ligands can be stripped without initiating agglomeration. These insights provide a framework for optimizing solvent‐mediated ligand exchange, with implications for NP applications in catalysis, energy storage, optoelectronics, and biomedical engineering.